PENGARUH MOTIVASI DAN LINGKUNGAN KELUARGA TERHADAP MINAT BERWIRAUSAHA ONLINE IBU RUMAH TANGGA DI KOTA PEKANBARU - Nurul Sukriani; Febrina Dian (Sekolah Tinggi Ilmu Ekonomi Riau, 2026)
Abstract:This study aims to examine the influence of motivation and family environment on the online entrepreneurial interest of housewives in Pekanbaru City. The rapid development of the digital economy has created opportunities for housewives to engage in online businesses as an alternative source of household income. However, the level of entrepreneurial interest varies among individuals and is influenced by several factors, particularly motivation and family environment. This study employed a quantitative approach using a survey method. The population consisted of housewives residing in Pekanbaru City who were interested in or actively engaged in online businesses. The sample was selected using a purposive sampling technique, involving 97 respondents. Data were collected through a Likert-scale questionnaire and analyzed using multiple linear regression with SPSS version 26. The results indicate that motivation has a positive and significant effect on online entrepreneurial interest, with a t-value of 7.717 and a significance level of 0.000 (p < 0.05). In contrast, the family environment does not have a significant effect on online entrepreneurial interest, as indicated by a t-value of -0.115 and a significance level of 0.909 (p > 0.05). Simultaneously, motivation and family environment have a significant effect on online entrepreneurial interest, as evidenced by an F-value of 51.796 and a significance level of 0.000 (p < 0.05). The Adjusted R² value of 0.514 indicates that 51.4% of the variance in online entrepreneurial interest can be explained by the two independent variables, while the remaining 48.6% is influenced by other factors not included in this study. Therefore, motivation is identified as the dominant factor influencing the online entrepreneurial interest of housewives in Pekanbaru City.